THE EFFECT OF USING ANIMATED ENGLISH MOVIE ON STUDENTS’ VOCABULARY MASTERY AT MTsN 3 KUANSING - Aprilia, Iltha; Gushendra, Rizky (State Islamic University of Sultan Syarif Kasim Riau, 2025)
This study aims to investigate the effect of using animated English movies on students’ vocabulary mastery at MTsN 3 Kuansing. A pre-experimental design with one group pre-test and post-test was applied, involving 30 eighth-grade students. The research instrument was a vocabulary worksheet (LKPD) which assessed six indicators: grammar, meaning, synonyms, antonyms, affixes, and word structure. The findings revealed a significant improvement in students’ vocabulary mastery after the treatment using Dora the Explorer animated movie. The average pre-test score was 54.17, while the post-test average rose to 78.67. Paired Sample T-Test analysis showed a significance value of 0.000 (< 0.05), indicating that the use of animated English movies had a statistically significant effect on vocabulary mastery. This research confirms the effectiveness of using multimedia, especially animated films, in enhancing vocabulary acquisition in junior high school students.